2020
DOI: 10.3390/cryst10100876
|View full text |Cite
|
Sign up to set email alerts
|

Cementitious Behavior of Argon Oxygen Decarburization Stainless Steel Slag and Its Stabilization on Chromium

Abstract: The study mainly aims at the potential of Argon Oxygen Decarburization Slag (AODS) as a supplementary cementitious material and explores the mechanisms of stabilization/solidification (S/S) of chromium in cement-based composite pastes. The basic cementitious parameters, such as water requirement, setting time, soundness, hydration characteristics, and strength indexes of composite binders, were examined through standard methods. The results showed that the most beneficial mineral phase in AODS for cementitious… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…The FTIR spectra of carbonated AOD slag at different temperatures were shown in Figure 7. Characteristic infrared vibration peaks were detected at 713 cm −1 , 871 cm −1 , 1421-1481 cm −1, and 1805 cm −1 in carbonated AOD slags [19] corresponding to the C-O stretching vibration peak, C-O anti-symmetric stretching vibration peak, CO 3 2− out-ofplane deformation vibration peak, and CO 3 2− in-plane deformation vibration peak of CaCO 3(C) , it showed that calcite (CaCO 3(C) ) was formed in the carbonated AOD slag at different temperatures. It was worth noting that the carbonated AOD slag still had a characteristic infrared vibration peak at 858 cm −1 at 80 • C and 100 • C, corresponding to the CO 3 2− out-of-plane bending vibration in aragonite (CaCO 3(A) ).…”
Section: Ftir Analysismentioning
confidence: 98%
“…The FTIR spectra of carbonated AOD slag at different temperatures were shown in Figure 7. Characteristic infrared vibration peaks were detected at 713 cm −1 , 871 cm −1 , 1421-1481 cm −1, and 1805 cm −1 in carbonated AOD slags [19] corresponding to the C-O stretching vibration peak, C-O anti-symmetric stretching vibration peak, CO 3 2− out-ofplane deformation vibration peak, and CO 3 2− in-plane deformation vibration peak of CaCO 3(C) , it showed that calcite (CaCO 3(C) ) was formed in the carbonated AOD slag at different temperatures. It was worth noting that the carbonated AOD slag still had a characteristic infrared vibration peak at 858 cm −1 at 80 • C and 100 • C, corresponding to the CO 3 2− out-of-plane bending vibration in aragonite (CaCO 3(A) ).…”
Section: Ftir Analysismentioning
confidence: 98%
“…The chemical composition of stainless steel slag is dependent on various factors (such as the smelting process, chemical compositions of raw materials, and target steel). Table 4 [51,[54][55][56][57][58][59][60][61] lists the chemical composition of typical stainless steel slag. As shown in Table 4, the oxides of Ca, Si, and Mg are the main components in stainless steel slag, and the rest are small amounts of oxides of Al, Mn, Cr, and Fe.…”
Section: Stainless Steel Dustmentioning
confidence: 99%
“…The form of Cr element in the stainless steel slag changes with the smelting processes. Many researchers reported that the Cr element in the EAF slag mainly exists in the form of a Cr-containing alloy, a Cr-containing spinel, and Cr 2 O 3 , while it mainly exists in the form of Cr-containing spinel in the AOD slag [57][58][59][60]64].…”
Section: Stainless Steel Dustmentioning
confidence: 99%
“…It is conducive to collection and processing and has reasonable prospects for recycling in concrete engineering and road engineering. In an earlier study, Rosales et al [ 7 ] analyzed the composition of AOD slag and found that its composition was similar to ordinary Portland cement and that it had certain cementitious activity [ 8 , 9 , 10 ]. Adegoloye et al [ 11 , 12 ] used AOD slag instead of natural aggregate in concrete and found that it can slightly improve the mechanical properties of concrete.…”
Section: Introductionmentioning
confidence: 99%